Rânula congénita. - Maria Inês Marques; Sofia Morais; Sílvia Coutinho; Ochoa de Castro; Ana Isabel Rei (Acta Médica Portuguesa, 2010)
The authors describe a case of congenital ranula diagnosed by a routine prenatal ultrasonography at 21 weeks of gestation. The fetal kariotype was normal. Follow-up ultrasound scans revealed no changes in the size or the position of the cyst. Fetal growth was normal as was the amniotic fluid volume. Surgical treatment was performed 3 days after a normal vaginal delivery, with excellent results.